2012
DOI: 10.3366/cor.2012.0025
|View full text |Cite
|
Sign up to set email alerts
|

Male and female shame: a corpus-based study of emotion

Abstract: In this study, I investigate the representation of the emotion terms shame, ashamed and shameless in relation to women and men in late twentieth-century British English. The study is based on analyses of examples of shame retrieved from the British National Corpus with the specific aim to study in what contexts men and women express shame or are associated with it, and evaluate whether the emotion is represented as negative or positive. I present two general models of shame, where the first model concentrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Research has suggested that whereas men experience more powerful emotions, women report more powerless emotions such as sadness and fear (Fischer, Rodriguez, Vianen & Manstead, 2004). Similarly, the presence of remorseful emotions such as 'worried', 'scared', and 'upset' supports previous assertions detailing greater intensity of negative emotions amongst women, particularly those linked to pain in relation to feelings of shame as a result of societal expectations (Norberg, 2012) As well as theoretical advancement, the findings can also offer practical uses for practitioners and experts within the justice system. Police officers working with women offenders could utilise the findings to enhance their knowledge of women offenders.…”
Section: Criminal Narrative Experience (Emotions and Roles)supporting
confidence: 59%
See 1 more Smart Citation
“…Research has suggested that whereas men experience more powerful emotions, women report more powerless emotions such as sadness and fear (Fischer, Rodriguez, Vianen & Manstead, 2004). Similarly, the presence of remorseful emotions such as 'worried', 'scared', and 'upset' supports previous assertions detailing greater intensity of negative emotions amongst women, particularly those linked to pain in relation to feelings of shame as a result of societal expectations (Norberg, 2012) As well as theoretical advancement, the findings can also offer practical uses for practitioners and experts within the justice system. Police officers working with women offenders could utilise the findings to enhance their knowledge of women offenders.…”
Section: Criminal Narrative Experience (Emotions and Roles)supporting
confidence: 59%
“…Regarding intensity, women described more undesirable and intense affective states connected to pain when explaining shame. However, men defined shame as an inevitable emotion evoked due to adhere to public perceptions, yet they did not report any links to pain with this affective state (Norberg, 2012).…”
Section: Affective Importance In Experiencementioning
confidence: 99%
“…Similarly, explorations of occurrence of shame between men and women also highlighted gender differences. Women reported experiencing greater intensity and more negative emotions linked to pain in relation to feelings of shame, whereas men described shame as a necessity to conform to societal expectations but did not detail pain with this emotion (Norberg, ). Research by Chaplin and Aldao () highlighted gender differences in relation to expression of emotion.…”
Section: Emotions and Gendermentioning
confidence: 99%
“…Corpus data have also been used to study differences in the way individual words are used and understood in association with females and males. My study of the representation of shame in the BNC (Norberg 2012) suggests that female shame is commonly related to physical unattractiveness, sexuality, exposure, and personal shortcomings, whereas male shame is more typically connected to physical and mental weakness. Stubbs’s (1996) study of the word happy in a scout leader’s speeches to young scouts shows that even a seemingly neutral emotion word may, as problematized by Baker (2006:6), be used asymmetrically with respect to gender.…”
Section: Gender and Corpus Linguisticsmentioning
confidence: 99%